From the Cacti Roses Grow: Eco-Governance Turning Political Desert Land to Urban Oases - Rami Elhusseini (Universitas Diponegoro, 2025)
This study revisits the Arsaali paradox, and the long-standing conflict rooted in the transformation of Arsaal, the largest village of Lebanon’s arid Hermel region, from a traditional agropastoral landscape into an unlikely mosaic of stone fruit orchards. What initially appeared to be a promising agricultural innovation disrupted the fragile equilibrium of miniature transhumance practiced by tribal herders, whose livelihoods depended on the sparse, endemic flora of the quasi-desert. While the orchards paradoxically revitalized local arid agriculture, they gradually displaced pastoral systems, igniting deep sociopolitical unrest. Over two decades ago, the American University of Beirut (AUB), through its Environment and Sustainable Development Unit (ESDU), helped mediate this transformation by fostering participatory land-use planning and cooperative development. The resulting truce withstood even the early years of the Syrian refugee influx and Lebanon’s growing governance vacuum. Today, however, the paradox returns with renewed vigor and pernicious mutations. Intensified climate change, urban sprawl, and accelerating land degradation now threaten not only livelihoods but entire ecosystems. Unregulated pollution, groundwater over-extraction, and veterinary collapse risk exterminating endemic species, alongside the vulnerable human communities sustaining this spiral. In response, AUB re-engages with nature-based solutions, such as Azolla-based wastewater treatment and horizontal-flow constructed wetlands, to restore ecological health, support transhumance traditions, and revive endemic plant and animal life. This strategy anchors biodiversity as a cornerstone of both conservation and peacebuilding. Promoting community stewardship through participatory action research, is grounded in the symbolic legacy of the Kamouh of Hermel, an ancient Pyramid styled mausoleum standing tall amid Hermel’s desert, mystically fusing Seleucid and Assyrian cultures. Our study reframes environmental recovery as a pathway to local empowerment and governance reform in Lebanon’s marginalized hinterlands. We call it Eco-Governance.